Polymorphism of the FaOMT and FaFADl genes for fruit flavor volatiles in strawberry varieties and wild species from the genetic collection of the Michurin Federal Research Center - A. S. Lyzhin; I. V. Luk’yanchuk; E. V. Zhbanova (Вавиловский журнал генетики и селекции, 2020)
Fruit aroma is an important consumer attribute of strawberry varieties. The key volatile compounds of the aromatic complex of strawberry fruit are mesifurane (fruity and caramel aromas) and y-decalactone (fruity, sweet, or peachy aroma). The mesifurane content in strawberry fruit is controlled by the FaOMT gene, which is mapped to the distal region of the long arm of chromosome VII-F.1. The y-decalactone content in strawberry fruit is controlled by the FaFADl gene, mapped to the distal region of the long arm of chromosome III-2. Identification of forms carrying genes for fruit flavor volatiles is an important step in breeding varieties with fragrant fruit. The use of molecular markers allows highly reliable detection of target gene alleles in a genome at early developmental stages. This study involves molecular genotyping of Fragaria L. varieties for the FaOMT and FaFADl genes, analysis of polymorphism of the loci in question, and identification of genotypes valuable for breeding. The objects of our study were wild species of the genus Fragaria L. and strawberry varieties (Fragariax ananassa Duch.) of different ecological and geographic origins. To assess the allelic states of the FaOMT gene, the codominant marker FaOMT-SI/NO was used, and for the FaFADl gene, the dominant marker FaFAD1. The functional allele of the FaOMT gene (FaOMT+) in the heterozygous state (FaOMT+FaOMT- genotype) was detected in 34.9 % of the accessions tested. The functional allele of the FaOMT gene in the homozygous state (FaOMT+FaOMT+ genotype) was detected in 51.2 % of the accessions. The homozygous state of the inactive allele (FaOMT-FaOMT- genotype) was detected in 13.9 % of the studied strawberry accessions. The FaFADl gene was identified in 25.6 % of the analyzed collection of strawberry genotypes, including the wild species F. orientalis Los., F. moschata Duch., F. ovalis Rydb. The combination of functional alleles of the FaOMT and FaFADl genes was detected in 16.3 % of the analyzed forms. The wild species F. orientalis Los. and F. moschata Duch. and strawberry variety Red Gauntlet combine the functional allele of the FaFADl gene with the homozygous state of the active allele of the FaOMT gene; therefore, we recommend them as promising sources of high contents of mesifurane and y-decactone in fruit in breeding programs for fruit aroma.